(untitled) (Boston, 2002)
Microarray technology is a major experimental tool for functional genomic explorations, and will continue to be a major tool throughout this decade and beyond. The recent explosion of this technology threatens to overwhelm the scientific community with massive quantities of data.
Keywords: DNA microarrays,Di truyền vi sinh; Xử lý dữ liệu; Data processing